Study on mechanism of matrine in treatment of COVID-19 combined with liver injury by network pharmacology and molecular docking technology - Fangzhou Liu; Yuanbai Li; Yang Yang; Meng Li; Yu Du; Yiying Zhang; Jing Wang; Yujing Shi (Taylor & Francis Group, 2021)
The aim of the present study was to investigate the pharmacological mechanism of matrine in treatment of COVID-19 combined with liver injury. Potential targets related to matrine, COVID-19 and liver injury were identified from several databases. We constructed PPI network and screened the core targets according to the degree value. Then, GO and KEGG enrichment were carried out. Molecular docking technology was used to verify the affinity between matrine and the crystal structure of core target protein. Finally, real-time RT-PCR was used to detect the effects of matrine on hub gene expression in liver tissue of liver injury mice and lung tissue of lung injury mice to further confirm the results of network pharmacological analysis. The results show that six core targets including AKT1, TP53, TNF, IL6, BCL2L1 and ATM were identified. The potential therapeutic mechanism of matrine on COVID-19 combined with liver injury is closely related to regulate antiviral process, improve immune system and regulate the level of inflammatory factors. Molecular docking showed that matrine could spontaneously bind to the receptor protein and had strong binding force. Real-time RT-PCR demonstrated that matrine could significantly reduce the expression of AKT1, TP53, TNF, IL6 and ATM in mice with liver injury or lung injury (P < 0.05), and increase the expression of BCL2L1 to a certain extent (P > 0.05). Our results indicate that matrine can achieve simultaneous intervention of COVID-19 combined with liver injury by multi-dimensional pharmacological mechanism.